(3WQb GdWYf aj GdeMQQGJ GdYQajI hhSGFd GdMO efgG aj GdehGO GdeOfjI GdJLGQjI (B/s - (3GdYRGRj, LeGd YRGRj eMeOs ([(3ecGf GdfTQ ZjQ eMOO(B] :s [(3GdfGTQ ZjQ eMOO(B](3,s, 2012)
(3jJeJY bGfhf GdEKHGJ HTcd YGe HCgejI HGdZI GdCKQ dOi GdeTJZdjf HGdbGfhf, abgGA hbVGI heMGejf heJbGVjf, aGdOdjd gh GdPj jMji GdMb hjMejg, hGdMb jJLQO ef bjeJg eG de jbe GdOdjd Ydi hLhOg bGfhfjG cGf Ch eGOjG, haj gPG GdHjGf JJLdi bOQGJ GdOaGY aj EHQGR ehVhY GdOYhi hjSJWjY Cf jbOQ fSHI fLGM OYhi ehcdg, HeLQO eYQaJg ddCOdI hGdCSGfjO GdJj jQJcR EdjgG eSJYjfG HGdbGfhf GdefWHb eJeScG Hg ajg dKHGJ gPg GdOYhi(B.s
(3bGFeI eNJUQGJ (B: (3UaMI (B611-612.s
(3HHdjhLQGajI (B: (3UaMI (B581-609.s
Keywords: (3GdJRhjQs -- (3bhGfjf hJTQjYGJs; (3GdWYf aj GdCMcGes; (3bGfhf GdELQGAGJ GdeOfjI hGdJLGQjIs